2015
DOI: 10.1038/ncomms9168
|View full text |Cite
|
Sign up to set email alerts
|

Robust production of recombinant phosphoproteins using cell-free protein synthesis

Abstract: Understanding the functional and structural consequences of site-specific protein phosphorylation has remained limited by our inability to produce phosphoproteins at high yields. Here, we address this limitation by developing a cell-free protein synthesis (CFPS) platform that employs crude extracts from a genomically recoded strain of Escherichia coli for site-specific, co-translational incorporation of phosphoserine into proteins. We apply this system to the robust production of up to milligram quantities of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
94
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 108 publications
(99 citation statements)
references
References 43 publications
(60 reference statements)
3
94
0
Order By: Relevance
“…The amino acid compositions were listed in Table 1 (MS spectra were listed in Fig.S2-S10). When the total tRNA was added, tyrosine, glutamine, lysine, and glycine were detected which is consistent with the previous report [22]. Additionally, we detected serine residue at position 151 in the PURE reaction which may result from the dephosphorylation of Sep. With ∆QYK tRNAs added, we did not detect tyrosine, glutamine, and lysine residues at position 151, and the MS quality was improved for Sep incorporation (Figure S7 and S8).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…The amino acid compositions were listed in Table 1 (MS spectra were listed in Fig.S2-S10). When the total tRNA was added, tyrosine, glutamine, lysine, and glycine were detected which is consistent with the previous report [22]. Additionally, we detected serine residue at position 151 in the PURE reaction which may result from the dephosphorylation of Sep. With ∆QYK tRNAs added, we did not detect tyrosine, glutamine, and lysine residues at position 151, and the MS quality was improved for Sep incorporation (Figure S7 and S8).…”
Section: Resultssupporting
confidence: 91%
“…Previous studies showed that the contamination of canonical amino acids at amber codons in CFPS systems is mainly from glutamine, as well as low level of tyrosine, glutamate, lysine, and glycine [22, 24], which is reasonable because codons for tyrosine (UAU and UAC), lysine (AAG), glutamine (CAG) and glutamate (GAG) have only one nucleotide difference from amber codon (UAG). In E. coli , there is only one species of tRNA isoacceptor for glutamate and lysine, respectively, while tyrosine and glutamine have two species of tRNA isoacceptors, individually [31].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, photocaged (Wu et al, 2004), fluorescent (Summerer et al, 2006), and bio-orthogonal reactive (Chin et al, 2002a,b; Lang et al, 2012) ncAAs have provided new ways to study protein structure and dynamics (Liu and Schultz, 2010). In addition, ncAAs that mimic natural post-translational modifications have helped to elucidate the role of such modifications in previously unattainable ways (Bröcker et al, 2014; Davis and Chin, 2012; Lee et al, 2013; Neumann et al, 2009; Oza et al, 2015; Park et al, 2011; Tian et al, 2014). Further, ncAA incorporation into proteins has opened the way to novel antibody drug conjugates (Axup et al, 2012; Zimmerman et al, 2014), modified human therapeutics (Cho et al, 2011), and protein biomaterials (Albayrak and Swartz, 2014), among other applications.…”
Section: Introductionmentioning
confidence: 99%